Surviving Through Tactics: The Everyday Life of Syrian Refugees in Turkey - Hülür, A. Banu; Ekinci, Yusuf; Deniz, A. Çağlar (Poligrafi, 2021)
The Syrian civil war and related migration affected Turkish border cities such as Antakya, Şanlıurfa, Mardin, Gaziantep, and Kilis. In this study, we explore the tactics and strategies developed by Syrian asylum seekers in order to cope with the prejudices and negative perceptions about Syrians commonly shared by locals. The findings of our research are drawn from the in-depth interviews we conducted with more than one hundred refugees, locals, and staff members of different NGOs. Our arguments and conclusions in this article are also the result of observations made during several research trips and a thorough examination of news about refugees in local and national media. Our field research lasted from August 2014 to February 2015, but the substantial part of this study was conducted between January and February 2015.